Pengembangan Sistem Informasi Stock Opname Berbasis Web Menggunakan Metode Saw - Rahmat Abdul Sahid Rahmat; Ahmad Nursodiq (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
This research presents the development of a web-based Stock Opname Information System integrated with the Simple Additive Weighting (SAW) method to support inventory decision-making at PT Sikat Bersih Indonesia. The existing stock opname process relies on spreadsheet-based recording, which increases the possibility of data inconsistencies, delays in reporting, and difficulties in identifying procurement priorities. The application was developed using the Waterfall software development model and implemented with PHP and MySQL. The SAW method evaluates inventory items using three criteria: Level of Need, Usage Frequency, and Remaining Stock. The developed application centralizes stock opname data, streamlines report generation, and produces objective recommendations for procurement priorities. Functional testing using the Black Box Testing approach confirmed that every feature operated as expected. These results indicate that the proposed system can effectively support stock opname activities and improve decision-making related to inventory management.